Features of albendazole determination and dynamics of its decomposition in biological material - V.K. Shormanov; D.P. Shcherbakov; S.Yu. Garmonov (Учёные записки Казанского университета: Серия Естественные науки)
Albendazole ([5-(propylthio)-1H-benzimidazol-2-yl]carbamic acid methyl ester) is a benzimidazole derivative drug that has anthelmintic activity and is especially effective against various nematodes. Along with pronounced pharmacological action, this compound is toxic to humans. Cases of poisoning with this substance and other benzimidazole derivatives are not uncommon. Despite the active use of albendazole in medical practice and its toxicity, many questions of the chemical and toxicological analysis of albendazole remain practically unexplored. In this regard, it is advisable to study albendazole in chemical and toxicological terms. This paper aims to analyze the determination and dynamics of albendazole decomposition in biological material. Acetone was used as a chemical agent for albendazole isolation from the liver as a biomaterial. Purification of the obtained extracts was carried out sequentially in a column (190 × 11 mm) of silica gel L 40/100 μm (eluent – acetone-methylene chloride (9:1)) and by liquid-liquid extraction. The methods of thin-layer chromatography (TLC), high-performance liquid chromatography combined with tandem mass spectrometry (HPLC-MS/MS), UV spectrophotometry were used for identification. The quantitative content of the analyte was determined using UV spectrophotometry by the absorption of the dimethylformamide (DMF) medium at 301 nm. The level of albendazole extraction from the biomaterial was 85–88%. Using the selected optimal conditions for isolation and purification, the dynamics of albendazole decomposition of in the biomaterial was studied based on the model mixtures with liver tissue stored at different temperatures. It was established that albendazole was still present in the biological material at temperatures of 0–2 °C, 8–10 °C, 18–22°C for at least 36 weeks.